Vermittlung der Abtönungspartikeln im DaF-Unterricht - Duch-Adamczyk, Justyna (Glottodidactica, 2012)
This paper is an attempt to present German modal particles in language education. The author describes the theoretical basis of teaching of modal particles on different levels and formulates the main problems of teaching and learning modals particles.